MRI-Based Assessment of Intralesional Delivery of Bone Marrow-Derived Mesenchymal Stem Cells in a Model of Equine Tendonitis - Alexandra Scharf; Shannon P. Holmes; Merrilee Thoresen; Jennifer Mumaw; Alaina Stumpf; John Peroni (Hindawi Limited, 2016)
Ultrasound-guided intralesional injection of mesenchymal stem cells (MSCs) is held as the benchmark for cell delivery in tendonitis. The primary objective of this study was to investigate the immediate cell distribution following intralesional injection of MSCs. Unilateral superficial digital flexor tendon (SDFT) lesions were created in the forelimb of six horses and injected with 10 × 106 MSCs labeled with superparamagnetic iron oxide nanoparticles (SPIOs) under ultrasound guidance. Assays were performed to confirm that there were no significant changes in cell viability, proliferation, migration, or trilineage differentiation due to the presence of SPIOs. Limbs were imaged on a 1.5-tesla clinical MRI scanner postmortem before and after injection to determine the extent of tendonitis and detect SPIO MSCs. Clusters of labeled cells were visible as signal voids in 6/6 subjects. Coalescing regions of signal void were diffusely present in the peritendinous tissues. Although previous reports have determined that local injury retains cells within a small radius of the site of injection, our study shows greater than expected delocalization and relatively few cells retained within collagenous tendon compared to surrounding fascia. Further work is needed if this is a reality in vivo and to determine if directed intralesional delivery of MSCs is as critical as presently thought.